Huff and Puff have too much stuff! - Rabe, Tish (I can read book., 2014)
"Huff pulls the train. Puff pushes the train. Together they can haul a lot. Big stuff, small stuff, they've got it all! But what happens when the best friends realize that they're stuck with too much stuff? Farmer Fluff has just the solution! Simple rhyme and easy-to-read verse will help beginning readers and train lovers build their vocabulary and strengthen reading skills."--Book jacket.